ABO Blood Group. Related Investigations and Their Association with Defined Pathologies - Ursula Jesch; P. Christian Endler; Beatrix Wulkersdorfer; Heinz Spranger (The Scientific World Journal)
The ABO blood group system was discovered by Karl Landsteiner in 1901. Since then, scientists have speculated on an association between different pathologies and the ABO blood group system. The aim of this pilot study was to determine the significance between different blood types of the ABO blood group system and certain pathologies. We included 237 patients with known diagnosis, blood group, sex, and age in the study. As a statistical method, the Chi-square test was chosen. In some cases, a significant association between the blood groups and defined diseases could be determined. Carriers of blood group O suffered from ulcus ventriculi and gastritis (X21 = 78.629, p <0.001), colitis ulcerosa and duodenitis (X21 = 5.846, p < 0.016), whereas male patients carrying blood group A tended to contract different types of tumours. In patients with intestinal tumours, females with blood group A were more likely to develop the pathology, whereas in males, the blood group O dominated. The development of cholelithiasis was found, above all, in patients with blood group O, which differed from other research where a correlation between this pathology and blood group A was found.